Learner Autonomy in the Moroccan Baccalaureate Classroom: Instructors' and Students' attitudes - Ezzaidi, Mohamed (Vivid: Journal of Language and Literature, 2022)
Autonomous learning as a concept has been around since the early 1960s. Several studies have been carried out to establish its relevance, practicability, and efficacy in the EFL course. However, its use in circumstances other than those in which it first emerged has provoked passionate discussion. While some applied linguists say that learner autonomy is insufficient outside of its native environment as a culturally restricted feature, others feel it is a humanistic attribute that can be employed in any situation. Local instructors' perspectives are not an exception in the Moroccan EFL context. Some teachers feel that educating students to accept autonomy will have a positive impact. Others, on the other hand, dismiss its significance due to administrative constraints and cultural differences. The purpose of this study is to learn more about Moroccan TEFLRS’ thoughts on student autonomy and how it is used in the local classroom. The study also shows how students think about learner autonomy and provides some suggestions for practicing it in the classroom.